Investigation and experiment of radar systems in unmanned arial vehicles-II - Ang, Kang Hong (2013)
Everyone knows the importance of defending our country and one of the key aspects of country defence is the military technology. There are also different types of defence technologies and some of the most commonly talked-about military technology includes the Unmanned Aerial Vehicle (UAV) and the Synthetic Aperture Radar (SAR) which is the topic of this project.